2016
DOI: 10.1039/c6tc03422e
|View full text |Cite
|
Sign up to set email alerts
|

New Y2BaAl4SiO12:Ce3+ yellow microcrystal-glass powder phosphor with high thermal emission stability

Abstract: or ''single-crystal phosphor''.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Nowadays, w-LEDs based on down-conversion phosphors (Y,Gd) 3 (Al,Ga) 5 O 12 :Ce 3+ plus a InGaN blue chip have become the common solid-lighting devices owning to its characteristics of high efficiency, long lifetime, rare pollution, etc. [1][2][3][4] However, the poor color rendering resulted from the deficiency of the red component has already restricted and hindered its further application in some certain fields. [5][6][7] Although co-doping rare earth ions (Pr 3+ , Eu 3+ , Sm 3+ , etc) or transition metal ions (Mn 2+ ) could inject more red component, the augment is quite limited and the thermal stability is significantly decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, w-LEDs based on down-conversion phosphors (Y,Gd) 3 (Al,Ga) 5 O 12 :Ce 3+ plus a InGaN blue chip have become the common solid-lighting devices owning to its characteristics of high efficiency, long lifetime, rare pollution, etc. [1][2][3][4] However, the poor color rendering resulted from the deficiency of the red component has already restricted and hindered its further application in some certain fields. [5][6][7] Although co-doping rare earth ions (Pr 3+ , Eu 3+ , Sm 3+ , etc) or transition metal ions (Mn 2+ ) could inject more red component, the augment is quite limited and the thermal stability is significantly decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, when the concentration of Mn 4+ ions increased, the lifetimes showed a downward tendency, because that the enhanced Mn 4+ concentration made the distance between activators become much closer, thus raising the probability of energy transfer between Mn 4+ ions. 53 Importantly, the IQE and EQE of the LMS:0.6Mn 4+ phosphors can be determined by the following expressions: 54,55…”
Section: Resultsmentioning
confidence: 99%
“…13 Ji et al reported the Y 2 BaAl 4 SiO 12 :Ce 3+ phosphor, with a bright yellow emission with a peak at 537 nm. 14 Shang et al researched the influence of Mg 2+ -Si 4+ /Ge 4+ incorporation into YAG, and the emission spectra could be regulated from 528 to 569 nm. 15 Another method is to introduce coactivated ions, which exhibit red emission.…”
Section: Introductionmentioning
confidence: 99%